(untitled) (Swiss Medical Weekly, 2015)
There is no doubt about the strong association of malnutrition and adverse medical outcomes including mortality, morbidity and quality of life. Particularly in the elderly and frail medical inpatient population, loss of appetite due to the acute illness further aggravates nutritional status. In fact, this relationship between acute disease and eating behaviour / nutritional status may well be bidirectional, with not only illness affecting nutritional status, but also dietary factors influencing the course of illness. Whether loss of appetite associated with acute illness is indeed a protective physiological response or a therapeutic target needing early corrective nutritional therapy is a matter of current debate and can only be resolved within a large and well-designed randomised controlled trial comparing early nutritional therapy with “appetite-guided” nutrition in this patient population. Apart from in critical care, where various large trials have recently been published, there is an important lack of high quality data from large randomised trials in unselected acutely ill medical inpatients to support the early use of nutritional therapy, to shed light on the optimal type, caloric amount and timing of nutritional therapy and to answer ultimately the question as to which patient population will in fact benefit from nutritional interventions. Currently, the EFFORT trial is enrolling patients and aims to fill these literature gaps. The aim of this review is to discuss the current evidence regarding nutritional therapy in acutely ill medical inpatients, and to recommend whether or not, based on today’s available evidence, physician should indeed encourage their malnourished patients to “…finish their lunch”.